Rapid stabilization of high-speed motion stage positioning oscillation using a vibration reduction unit - Zhang, Lanyu; Zhang, Shaoxuan; Gao, Jian; Zhang, Peiyuan; Feng, Fuyuan; Luo, Yuheng; Liu, Yachao (Precision engineering, 2025)
A high-speed motion stage with less settling time is essential for most microelectronics manufacturing equipment. Usually, high-speed motion induces overshoot and inertial vibration during the stage positioning process. To rapidly reduce the stage positioning oscillation, this paper proposes a novel vibration-reduction-unit (VRU) for speeding up the positioning stabilization of the stage. More precisely, the VRU includes a servo actuator, and it is installed on the fixed-end of the stage with maintaining a small-gap from the displacement output-end of the stage. During the deceleration positioning process of the stage, the VRU is actuated with optimal start-up condition to actively act on the stage with an acting force and interfere the stage inertial vibration. This start-up condition including the acting moment of the VRU is determined based on the in-time displacement. The theoretical relationship between the VRU acting force and the attenuation of the stage inertial vibration amplitude is clarified based on the dynamics and force analyses. The effects of different VRU acting forces on stage vibration reduction are examined through simulations. A series of experiments are conducted, and the results show that the proposed VRU can help the stage to significantly reduce the vibration amplitude and settle down rapidly. •A novel vibration reduction unit is proposed to speed up the positioning stabilization of motion stage.•A start-up condition is determined to properly actuate the vibration reduction unit for interfering the stage.•The efficiency of the positioning operation of the stage can be improved at the same high-speed movement.•A reduction of 74.6 % of the settling time of the stage can be achieved by using the vibration reduction unit.